2013
DOI: 10.1177/1359105313476977
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of obesity among Saudi Arabian women contemplating bariatric surgery: An interpretative phenomenological analysis

Abstract: This study explored experiences of obesity, its perceived causes, and motives for surgery, as described by seven Saudi women contemplating bariatric surgery. The women experienced cultural restrictions on their physical and social activities. Obesity embodied these restrictions, attracting stigma and moral failure. Traditional clothing, foods, hospitality norms, and limited outdoor female activities were regarded as barriers to weight loss.Bariatric surgery was chosen to protect health and to access normative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 25 publications
2
68
0
Order By: Relevance
“…In Saudi Arabia, the number of weight loss surgery cases has increased over the years and is likely to continue [16]. This could be due to the limited outdoor activities for females and the cultural restrictions from being physically and socially active [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the number of weight loss surgery cases has increased over the years and is likely to continue [16]. This could be due to the limited outdoor activities for females and the cultural restrictions from being physically and socially active [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, previous studies in Arab countries have reported that women in Arabic countries are restricted in their practice of outdoor activities due to cultural beliefs and traditional barriers (Alqout & Reynolds, 2014;Henry, Lightowler & Al-Hourani, 2004;Badran & Laher, 2011;Ali, Baynouna & Bernsen, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…This information may be used to enhance the existing BELT programme using participant feedback as a guide. As well as maintaining the consistent programme structure, a behavioural change intervention programme may specifically aim to increase participant knowledge about exercise and health; provide social support and foster a sense of community among programme participants; and address potential barriers while developing action plans to continue exercise upon programme completion . Similar programmes might be specifically structured with behavioural components to promote accountability and foster social support among participants, in addition to providing a supportive exercise setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients are typically made aware of the benefits of physical activity participation post‐bariatric surgery, many face barriers that make participation difficult . In fact, a recent meta‐analysis indicated that although step count typically increases 3 to 6 months following surgery, objectively measured MVPA decreases slightly .…”
Section: Introductionmentioning
confidence: 99%